The Effect of Poverty Levels and Minimum Wages on The Human Development Index in West Nusa Tenggara Province - Baehaqi; Erika Suryaningsih; Ahmad Suhendri (LP2M IAIN Palopo, 2026)
This study aims to determine how poverty levels and minimum wages affect the Human Development Index (HDI) in West Nusa Tenggara Province from 2010 to 2024. This study is quantitative in nature because it is numerical and uses multiple linear regression analysis. This study uses secondary data in the form of time series data for the period 2010-2024 obtained from the Central Statistics Agency (BPS). The results show that, partially, the poverty level variable has a negative and significant effect on the human development index variable in NTB in 2010-2024, while the minimum wage variable partially has a positive and significant effect on the Human Development Index variable in NTB in 2010-2024. Then, simultaneously, the poverty rate and minimum wage variables affect the Human Development Index in NTB in 2010-2024.